2020
DOI: 10.5812/semj.91033
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Massage Therapy with or without Physical Exercises on the Weight of Premature Infants Admitted to the Neonatal Intensive Care Unit: A Randomized Clinical Trial

Abstract: Background: The infants born before the 37th week of gestation are considered as preterm. Premature birth may have several consequences including low birth weight (LBW). Infants born with the weight below 2500 g are known as LBW. Birth weight can be a proper characteristic of healthy neonate. Integrated interventions, including massage, simulate uterus environment for direct growth of an infant through the target route; hence, such interventions can be beneficial to the premature infant. Objectives: Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
3
0
3
Order By: Relevance
“…However, there is a remarkable agreement in the literature regarding the symptoms commonly associated with food intolerance and operational definitions. These components are necessary to develop a standard of care that aims to encourage prudent reporting of early signs/symptoms of feeding intolerance to healthcare providers, which can improve neonatal outcomes (18,19) . However, little research showed the connection between intervention of abdominal massage and feeding intolerance in premature neonate.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a remarkable agreement in the literature regarding the symptoms commonly associated with food intolerance and operational definitions. These components are necessary to develop a standard of care that aims to encourage prudent reporting of early signs/symptoms of feeding intolerance to healthcare providers, which can improve neonatal outcomes (18,19) . However, little research showed the connection between intervention of abdominal massage and feeding intolerance in premature neonate.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the types of emollient oils used in the intervention groups, half of the studies employed coconut oil [ 15 , 26 , 27 , 38 ] or sunflower oil [ 22 , 29 , 31 , 32 ] as topical emollient therapies. The remaining studies utilized olive oil [ 25 , 28 , 30 ], Medium-chain triglyceride (MCT) oil [ 11 , 23 , 24 ], Soya oil [ 35 ], iSio4 [ 36 , 37 ], and Vimala [ 34 ] in their intervention groups. The duration of therapy for preterm neonates shows variation, spanning from 5 to 60 days, with an average duration of 18.5 days.…”
Section: Resultsmentioning
confidence: 99%
“…Selain itu pemijatan dapat memberikan efek rasa lapar akibat pengosongan lambung yang baik. Hormon yang terkait dengan proses pencernaan terutama stimulus rasa lapar akan bekerja dengan baik (Montaseri et al 2020) (Özdemİr 2019).…”
Section: Pendahuluanunclassified
“…hal ini karena tindakan tersebut dapat meningkatkan gerakan peristaltik usus yang berpengaruh terhadap proses buang air besar. rangsangan yang diberikan seperti rangsangan taktil dapat meningkatkan ornithine decarboxylase yang bertugas untuk sintesis protein sehingga berdampak pada peningkatan berat badan pada bayi dan balita (Majid and Rusmariana 2021; Özdemİr 2019)(Montaseri et al 2020). Teknik pemijatan pada bayi dan balita dalam posisi tengkurap dapat memberikan dampak positif terhadap system kardiopulmonalis.…”
unclassified